(untitled) (Chemical Engineering Research Bulletin, 2008)
Production of sodium hypochlorite was studied by the electrolysis of 4.0 molar sodium chloride solution using graphite anode and stainless steel cathode. The effect of current density, temperature, concentration of electrolyte, addition of dichromate and electrolyte volume on the production of hypochlorite and chlorate have been investigated. The performance of the cell has been assessed in terms of power consumption, current efficiency and space time yield. Chemical Engineering Research Bulletin 10 (2006) 1-10